Public policy applied in industry 4.0: a comparative study between Brazil and Canada focusing on information literacy - Capinzaiki Ottonicar, Selma Leticia [UNESP]; Pomim Valentim, Marta Ligia [UNESP]; Mosconi, Elaine (Univ Brasilia, Dept Ciencia Informacao, 2019)
Industry 4.0 has brought new transformations to the organizations. Therefore, many countries have applied public policies in order to contribute to the economic competitiveness. The purpose of this paper is to analyze the actions and public policies of Brazil and Canada, so organizations can innovate and be competitive in the context of industry 4.0. Furthermore, it aims to demonstrate the relevance of information literacy for individuals to access these policies. This paper is a comparative study that relies on a documentary research method about public policies and actions that focus on Industry 4.0 in Brazil and Canada. Primary information sources were considered between 2014 and 2018. We consulted official publications like government reports, National Strategy of Science, Technology and Innovation and Website. The results showed that both countries have made efforts to make companies aware of the results of the 4th Industrial Revolution and business opportunities. The conclusions indicate that Brazil needs to disseminate the idea of Industry 4.0 for businesses, so they can start to adapt in this new era. Canada needs more investment, especially for small businesses. Furthermore, both countries can benefit from an international partnership, so they can encourage exportation and information sharing.
Keywords: public policy; government actions; industry 4.0; comparative study; information literacy